Cerebral small vessel disease: A glymphopathy?. (February 2022) - Benveniste, Helene; Nedergaard, Maiken
Abstract: Small vessel disease (SVD) is a common instigator of dementia in the aging population. The hallmarks of SVD are enlargement of the perivascular spaces and white matter hyperintensities. The latter represents local fluid accumulation in white matter that either subsides or develops into lacunar infarcts. We here propose that failure of brain fluid transport—via the glymphatic system—plays a key role in initiation and progression of SVD. Our major case for this concept is that perivascular spaces are utilized as waterways for influx of cerebrospinal fluid. Stagnation of glymphatic transport may drive loss of brain fluid homeostasis leading to transient white matter edema, perivascular dilation, and ultimately demyelination. This review will discuss how glymphatic rodent studies of hypertension and diabetes have provided new insight into the pathogenesis of SVD. Highlights: SVD is a common and mechanistically poorly understood cause of dementia. SVD is characterized by enlarged perivascular spaces and white matter hyperintensities. Rodent models replicate only certain aspects of the clinical features of SVD. Glymphatic transport is moderately reduced in rodent models of hypertension and diabetes. Long-term stagnation of perivascular fluid transport represents a key aspect of SVD pathogenesis.